Coase-Stiglera’s theorem (economic theory of the property rights) - S. S. Repin (Путеводитель предпринимателя, 2020)
Coase-Stiglera’s theorem is important for development of the economic theory until the property rights are accurately reflected in transactions, it leads to decrease in efficiency of a market mechanism and to collision of intereks of various groups of economic subjects.